Peningkatan Kapasitas Kader Posyandu dalam Mendeteksi dan Mencegah Stunting di Jakarta Pusat - Lameky, Vernando Yanry; Harmanto, Harmanto; Tomasoa, Valesnya Yeslin (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2023)
Stunting is a condition that is increasingly observed in developing countries such as Indonesia, and is on the rise in developed countries. One in three children under the age of 5 is considered stunted, as stated by the United Nations International Children's Emergency Fund (UNICEF). the process of becoming short or stunting in children in a region or poor area starts as early as 6 months of age and continues until the age of 18 years. The incidence of stunting occurs in the first two to three years of life. Based on the phenomenon, the results of research and community service that detect and prevent stunting is one of them increasing the capacity of posyandu cadres. The purpose of this study was to increase the capacity of posyandu cadres in detecting and preventing stunting in the working areas of RW 02 and RW 03, Gunung Sahari Selatan Village, Kamayoran District, Central Jakarta. The research method is quantitative pre-experimental with a one group pretest-posttest design. The sampling technique used purposive sampling method, which was 80 respondents. The instruments in this study were questionnaires and observation sheets, while the tools and materials supporting the research were leaflet media and flip sheets. The results showed that all posyandu cadres in the gender category were female 80 respondents (100%), the age of the majority of posyandu cadres aged 31 years to 60 years, namely 40 respondents (50%), the most education of posyandu cadres was SMA, namely 50 respondents (62.5%), the length of time being a posyandu cadre was 5 years, namely 34 respondents (42.5%), chi-square analysis obtained a p value = 0.001 (? ? 0.05), so it can be concluded that there is a significant level of difference in the knowledge of posyandu cadres before and after training. All posyandu cadres are expected to be able to identify risk factors that cause stunting in the posyandu work area, and continue to receive continuous training that is periodic and programmed so that the increase in knowledge and skills is better.Keywords: Capacity Building; Posyandu Cadres; Stunting; Detect; Prevent